Identifikasi Keragaman Jenis Parasit Cacing pada Ternak Ayam Kampung di Kabupaten Jember - Satria Budi Kusuma; Suluh Nusantoro; Aan Awaludin; Yendri Junaidi; Tutik Lusyta Aulyani (Politeknik Negeri Jember, 2021)
Parasitic worms (Helminths) are the one of health problems related to the parasites investment that is often found in native chickens. This study aimed to identify the diversity of worm parasites found in native chickens in Jember Regency. The sampling procedure for native chicken excreta was carried out randomly. The excreta samples taken were 150 samples around Jember Regency. Identification of the diversity of worm species was carried out by examining worm eggs in excreta samples using the sedimentation method at BBVet (Balai Besar Veterinary) Wates, Yogyakarta. The parasitic worms identified in the excreta samples of native chickens were worms from the Nematode class consisting of Capillaria sp. (24.67%); Heterakis sp. (10.67%); Strongyloides sp. (3.33%); and Ascaridia sp. (2.67%).